Socialist Educational Policy in Autonomous Region of Kosovo and Metohija: Goals, Objectives and Ootcomes - Vukadinović, Igor (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
This research aims to shed light on the social challenges of school development in Kosovo and Metohija after the Second World War. It examines how the philosophy created in Soviet Union and Western Marxist circles was applied in nationally divided, predominantly agrarian, traditional society, with an extremely high illiteracy rate. The paper also shows how society is impacted when educational policy in a certain area becomes a means for achieving ideological goals. The study is grounded in the unpublished documents of the Archives of Yugoslavia, Archives of Serbia, and the Central State Archives of Albania.